Charming Billy - McDermott, Alice (New York : Delta Trade Paperbacks, 1999)
When the late Billy Lynch's relatives and friends gather together to keep his memory alive, stories are woven and memories relived detailing his life in the close Irish-American community and the intricate feelings that resurface.
Billy Lynch's family and friends have gathered to comfort his widow, and to pay their respects to one of the last great romantics. As they trade tales of his famous humor, immense charm, and consuming sorrow, a complex portrait emerges of an enigmatic man, a loyal friend, a beloved husband, an incurable alcoholic. Alice McDermott's striking novel, Charming Billy, is a study of the lies that bind and the weight of familial love, of the way good intentions can be as destructive as the truth they were meant to hide.
Keywords: Irish Americans -- New York (State) -- New York -- Fiction; Alcoholics -- New York (State) -- New York -- Fiction; Families -- New York (State) -- New York -- Fiction; Alcoholics -- Fiction; Family -- Fiction; Irish Americans -- Fiction; Bronx (New York, N.Y.) -- Fiction; amerikanske; romaner; 1990-tallet; Domestic fiction